Impact of occupational stress on performance metrics for women in Kerala’s police force - Sivadas, Kalpa; Rajalakshmi, K. (Edelweiss Applied Science and Technology, 2024)
Occupational stress is a prevalent issue impacting workers in diverse occupations, particularly prominent in high-pressure sectors like law enforcement. This study examines the factors that influence occupational stress amongst female police officers in Kerala, emphasizing the effects of these stressors on their job performance, physical and mental well-being, work-life balance, and plans to leave the profession. The study employed a mixed-methods approach, combining quantitative surveys with qualitative interviews to gather comprehensive data. Major findings indicate that the majority of officers are aged 31 to 40, generally married, and possess a high level of education, suggesting a combined load of professional and personal obligations. Multiple regression analysis results demonstrate that increased workload and time pressure substantially impair job performance. Furthermore, hierarchical regression analysis indicates that job role ambiguity intensifies anxiety and physical health issues. A significant relation between exposure to hazardous conditions and reduced work-life balance was discovered. Enhanced managerial assistance correlated with reduced absenteeism and turnover intentions, underscoring the vital need for proficient leadership. The results support organizational policies designed to reduce occupational stress, improve general well-being, and retain female police personnel.